E3 Ubiquitin Ligase in Anticancer Drugdsla Resistance: Recent Advances and Future Potential - Liu, Yuanqi; Duan, Chaojun; Zhang, Chunfang (Frontiers in Pharmacology, 2021)
Drug therapy is the primary treatment for patients with advanced cancer. The use of anticancer drugs will inevitably lead to drug resistance, which manifests as tumour recurrence. Overcoming chemoresistance may enable cancer patients to have better therapeutic effects. However, the mechanisms underlying drug resistance are poorly understood. E3 ubiquitin ligases (E3s) are a large class of proteins, and there are over 800 putative functional E3s. E3s play a crucial role in substrate recognition and catalyse the final step of ubiquitin transfer to specific substrate proteins. The diversity of the set of substrates contributes to the diverse functions of E3s, indicating that E3s could be desirable drug targets. The E3s MDM2, FBWX7, and SKP2 have been well studied and have shown a relationship with drug resistance. Strategies targeting E3s to combat drug resistance include interfering with their activators, degrading the E3s themselves and influencing the interaction between E3s and their substrates. Research on E3s has led to the discovery of possible therapeutic methods to overcome the challenging clinical situation imposed by drug resistance. In this article, we summarize the role of E3s in cancer drug resistance from the perspective of drug class.